The utilization of phase change material (pcm) composite derived from fatty acids and waste materials as thermal energy storage (tes) medium - Sumaiya, Zainal Abidin; Saidatul Shima, Jamari; S. A., A. Ghani (2018)
Implementation of organic materials in the thermal energy storage (TES) systems has been one of the most attractive candidates in improving the heat and energy storages as well as preserving the environment. Organic PCM such as fatty acid has been discovered to have high heat capacity, good chemical stability, low or non- supercooling, non-corrosive, small volume change, low vapor pressure and low cost. However, problem associated with low thermal conductivity has become one of the major drawbacks of PCM derived from fatty acids. Therefore, in-depth researches have been conducted and PCM composite containing fillers such as nanowires, metallic, and carbon additives has been formulated to investigate the potential of these materials to improve the performance of conventional organic PCM during heating and cooling application in solar system. As they observed the thermal properties between the formulated PCM composite, PCM with carbon additives has shown the obvious advantages but the other PCM fillers properties were excellent too. Despite their good performance, in terms of economic value, it is quite pricy. From the study, the performance of PCM composite using nanowires and metallic particles was poorer compared to the carbon additives (i.e. expanded graphite, graphene oxide, and activated carbon) during heating and cooling application in solar system. Despite that, the performance is still excellent for the thermal storage and thermal conductivity of all elements but, in terms of economic value, it is quite pricy. Therefore, several solutions have been identified to enhance the thermal conductivity of the conventional PCM whilst producing cheaper PCM composite.